De l'éducation des filles by Fenelon : women's social collective in the early twentieth century - Alberto Gálvez Toro (Universidad de Alicante, 2012)
This article proposes an analysis of Fenelon's De l'éducation des filles in its 1919 Spanish edition. The study has focused on three categories: the ideological one, which defines the social concept of woman at the time and in the text; the aesthetic one, which shapes the social image of a beauty ideal; and the praxical one, which establishes the action component of the collective and its social action. These three elements, separated and united around pedagogy, become intermingled into a whole that provides an image of woman at a specific period and within a specific society. The results are useful and can help to understand some of the aspects that surrounded the changes in women's social status during the period comprised between the late 19th century and the early 20th century.